Magnesium sulphate nebulization in acute bronchiolitis in infants: a randomized controlled trial - Janakwade, Shivhar K.; Pandit, Sadbhavana; Dhawan, Neeraj (International Journal of Contemporary Pediatrics, 2021)
Background: Acute bronchiolitis is a disorder of the lower respiratory tract that occurs mostly in between 1 month to 24 months. There are limited numbers of studies on magnesium sulphate nebulization in acute bronchiolitis. There is a desperate need for a standard treatment which can reduce the morbidity and mortality in acute bronchiolitis. The goal was to study the efficacy of magnesium sulphate nebulization in infants with acute bronchiolitis. Methods: It was a prospective open labelled randomized controlled study. Children in age group of 2-12 months admitted with clinical diagnosis of acute bronchiolitis in paediatric emergency ward, GMSH-16, Chandigarh. Study group patients were treated with 40 mg/kg magnesium sulphate nebulization diluted with 2-3 ml normal saline in addition to supportive treatment as oxygen and IV fluids, three doses of medication were given at 1 hour interval and it was not repeated after three doses. Control group patients were treated with oxygen therapy, IV fluids, symptomatic treatment for fever and supportive care. Results: Respiratory distress assessment instrument score and length of hospital stay was significantly lesser in study group as compared to control group. SpO2 was significantly more in study group as compared to control group. Conclusions: Magnesium sulphate nebulization is effective in improving respiratory distress and oxygen saturation, it also reduces duration of hospital stay in infants with mild to moderate bronchiolitis.